Pendugaan Potensi dan Pemanfaatan Perikanan Demersal Pantai Timur Provinsi Jambi - Alamsyah, Zulkifli; Soelistiowaty, Soelistiowaty (PROSIDING SEMINAR NASIONAL AGRIBISNIS, 2016)
This study aimed to estimate the potential for sustainable and resource utilization rate of demersal fisheries on the East Coast Jambi Province. According to the availability of data, this research using time series data for the period 2003 to 2012. Data were analyzed using the Gordon-Schaefer bioeconomic fisheries approach in the estimation of the potential for sustainable (maximum sustainable yield) and maximum sustainable catch on maximum sustainable yield. Moreover, predictions were also conducted to determine the effect of effort units (fishing trips) to catch per unit effort (CPUE). Fishing gear is used as the standard in estimation as it is the majority of coastal trawlers used by fishermen with the highest productivity of demersal fisheries compared to other fishing gear. The results show that the average production per unit effort over the analysis period observed was 116.05 tons/trip/year. The results of the estimation significantly show that the more the business units (efforts), the less catch per unit effort. The maximum sustainable yields (CMSY) is 41.10 thousand tons/year with a maximum Effort (EMSY) of 438 trips/year means that the potential maximum sustainable yields are allowed by 93.78 tonnes/trip/year. While economically, the maximum production rate (CMEY) is 31.8 thousand tonnes with a maximum effort (CMEY) is 230 trips/year. It can be concluded that the rate of utilization of demersal fishery resources in the East Coast area of Jambi Province during the period of 2003-2012, had been in the utilization of overfishing and economically is on the condition that do not provide maximum benefit to fishermen.